College-Based Support Programs for Students With Autism. (December 2020) - Viezel, Kathleen D.; Williams, Elizabeth; Dotson, Wesley H.
There has been an increase in the number of students with autism spectrum disorder (ASD) attending college. To support this growing population of students, institution-based support programs have developed across the country to promote college success by addressing the social, communication, and executive functioning needs of students with ASD. This study investigated the current state of college-based ASD support programs to analyze current standards of care while also disseminating cohesive program information to professionals and families involved in postsecondary planning. Trends in college-based ASD service provision, admission requirements, and administrative support were identified through a systematic search and examination of traditional 4-year colleges with ASD-specific supports.